Ethylene-Regulated Glutamate Dehydrogenase Fine-Tunes Metabolism during Anoxia-Reoxygenation. Issue 3 (27th September 2016) - Tsai, Kuen-Jin; Lin, Chih-Yu; Ting, Chen-Yun; Shih, Ming-Che
Abstract : Ethylene participates in the regulation of glutamate dehydrogenase genes during anoxia-reoxygenation and modulates metabolism by enhancing tricarboxylic acid cycle replenishment to aid recovery in Arabidopsis. Abstract: Ethylene is an essential hormone in plants that is involved in low-oxygen and reoxygenation responses. As a key transcription factor in ethylene signaling, ETHYLENE INSENSITIVE3 (EIN3) activates targets that trigger various responses. However, most of these targets are still poorly characterized. Through analyses of our microarray data and the published Arabidopsis ( Arabidopsis thaliana ) EIN3 chromatin immunoprecipitation sequencing data set, we inferred the putative targets of EIN3 during anoxia-reoxygenation. Among them, GDH2, which encodes one subunit of glutamate dehydrogenase (GDH), was chosen for further studies for its role in tricarboxylic acid cycle replenishment. We demonstrated that both GDH1 and GDH2 are induced during anoxia and reoxygenation and that this induction is mediated via ethylene signaling. In addition, the results of enzymatic assays showed that the level of GDH during anoxia-reoxygenation decreased in the ethylene-insensitive mutants ein2-5 and ein3eil1 . Global metabolite analysis indicated that the deamination activity of GDH might regenerate 2-oxoglutarate, which is a cosubstrate that facilitates the breakdown of alanine by alanine aminotransferase when reoxygenation occurs. Moreover, ineffective tricarboxylic acid cycle replenishment, disturbed carbohydrate metabolism, reduced phytosterol biosynthesis, and delayed energy regeneration were found in gdh1gdh2 and ethylene mutants during reoxygenation. Taken together, these data illustrate the essential role of EIN3-regulated GDH activity in metabolic adjustment during anoxia-reoxygenation.